Callus Induction of Porang Plants (Amorphophallus muelleri Blume) with 2,4- D on Various Explant Sources In Vitro - Haring, Feranita; Sjahril, Rinaldi; Khatima, Khusnul (Hasanuddin University, 2023)
This study aims to determine the effect of a concentration of 2,4-D added to the Murhasige and Skoog (MS) basic media on porang callus induction and the effect on various explant sources. The study was conducted in the form of experiments in the Laboratory of Bioscience and Plant Reproduction Biotechnology, Department of Agriculture, Faculty of Agriculture, Hasanuddin University from August to December 2021. The experiments were based on a Completely Randomized Design (CRD) pattern arranged in a factorial way with two treatment factors. The first factor was the concentration of 2,4-D consisting of five levels of treatment: without 2,4-D (0.0 mg L-1), 0.5 mg L-1, 1.0 mg L-1, 1.5 mg L-1, and 2.0 mg L-1. The second factor was the source of explants consisting of three levels: the petiole, leaf midrib, and leaf blade. The results after five months showed that the interaction between the concentration of 2.0 mg L-1Â 2,4-D with the petiole explants had the best effect on callus induction time (12.25 days) and callus weight (2.97 g). The concentration of 2.0 mg L-1Â 2,4-D had the best influence on the callus induction percentage (83.33%), and petiole-derived explants had the best influence on the callus induction percentage (91.67%). Administration of 2,4-D at a concentration of 2.0 mg L-1Â and the petiole-derived explant gave the best results in this study; therefore, it is expected to be applied to the development of porang plant seeds in vitro.